Estimating party policy positions: Comparing expert surveys and hand-coded content analysis - BENOIT, Kenneth (Institutional Knowledge at Singapore Management University, 2007)
In this paper we compare estimates of the left-right positions of political parties derived from an expert survey recently completed by the authors with those derived by the Comparative Manifestos Project (CMP) from the content analysis of party manifestos. Having briefly described the expert survey, we first explore the substantive policy content of left and right in the expert survey estimates. We then compare the expert survey to the CMP method on methodological grounds. Third, we directly compare the expert survey results to the CMP results for the most recent time period available, revealing some agreement but also numerous inconsistencies in both cross-national and within-country party placements. We conclude by investigating the CMP scores in more detail, focusing on the series of British left-right placements and the components of these scores.